2013
DOI: 10.1024/1421-0185/a000098
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Familiarity with a Judgmental Situation Improves Lie Detection Ability

Abstract: Lie catchers are often barely better than chance. In this experiment, we investigated the influence of manipulated perceived familiarity with a situation that measured participants’ ability to correctly classify lies and truths. As expected, participants in the high-familiarity condition showed substantially (21%) greater classification accuracy for both truths and lies than in the low-familiarity condition. Furthermore, as predicted, mediational analyses indicated that the higher classification accuracy rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 45 publications
(81 reference statements)
1
33
0
Order By: Relevance
“…Less proficient observers might not be in tune with their own verbal and nonverbal behaviors when speaking English, making it difficult for them to interpret these cues in others. Moreover, in previous studies, familiar observers were able to rely upon their previous experience with the critical event to aid their decisions (e.g., Reinhard et al, ). Having experience speaking in a non‐native language would not have provided observers with comparable additional information or insight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less proficient observers might not be in tune with their own verbal and nonverbal behaviors when speaking English, making it difficult for them to interpret these cues in others. Moreover, in previous studies, familiar observers were able to rely upon their previous experience with the critical event to aid their decisions (e.g., Reinhard et al, ). Having experience speaking in a non‐native language would not have provided observers with comparable additional information or insight.…”
Section: Discussionmentioning
confidence: 99%
“…In general, familiarity effects on deception detection have been inconsistent (Comadena, ; Feeley, deTurck, & Young, ; McCormick & Parks, ). High (vs. low) geographical familiarity substantially improved deception detection by increasing observers' reliance on diagnostic verbal content (Reinhard, Sporer, & Sharmach, ). Yet it was a U‐shaped function that best described the relationship between interpersonal familiarity and deception detection (Feeley et al, ).…”
Section: Proficiency and Deceptionmentioning
confidence: 99%
“…In a study with police officers, deception detection was improved when they focused on story-related cues, such as vagueness or contradictions, instead of nonverbal cues like posture change or fidgeting (Mann, Vrij, & Bull, 2004). Detection deception is also more accurate when judges are familiar with the situation described in the (truthful vs. deceptive) statement (Reinhard, Sporer, & Scharmach, 2015;Reinhard, Sporer, Scharmach, & Marksteiner, 2011). Similarly, judges provided with "content in context" cues, such as meaningful contextual information, reached an average of 75% detection accuracy (Blair, Levine, & Shaw, 2010).…”
Section: Impression Management Detectionmentioning
confidence: 98%
“…In a meta‐analysis, DePaulo, Charlton, Cooper, Lindsay, and Muhlenbruck () found that, although increased confidence was not associated with more accurate deception judgments, people tended to be more confident when judging true as opposed to deceptive accounts; that is, people expressed greater certainty in their judgments of actual truths (vs. lies), independently of whether or not they correctly identified them as true. Moreover, Reinhard, Sporer, and Scharmach (in press) recently found that confidence and lie detection accuracy were better calibrated when judges felt highly familiar (vs. unfamiliar) with the judgment situation. This suggests that meta‐cognitive experiences (e.g., confidence, accessibility experiences) may be valid indicators of truth and deception.…”
Section: Discussionmentioning
confidence: 99%